Thoracic spinal anesthesia with intrathecal sedation for lower back surgery: a retrospective cohort study - Boykov, Nikolay; Ferdinandov, Dilyan; Vasileva, Petra; Yankov, Dimo; Burev, Stefan; Tanova, Rositsa (Frontiers in Medicine, 2024)
Background: Spinal anesthesia (SA) is a good alternative to general anesthesia (GA) for spine surgery. Despite that, a few case series concern the use of thoracic spinal anesthesia for shortduration surgical interventions. In search of an alternative approach to GA and a better opioidfree modality, we aimed to investigate the safety, feasibility, and patient satisfaction of thoracic SA for spine surgery.Material and Methods: We analyzed retrospectively a cohort of 24 patients operated on for a degenerative and osteoporotic pathology of the lower thoracic and lumbar spine. Data was collected from medical records, including clinical notes, operative and anesthesia records, and patient questionnaires.Results: Twenty-one surgeries for herniated discs, two for degenerative spinal stenosis, and one for multi-level osteoporotic vertebral body fractures were performed under spinal anesthesia with intrathecal sedation. In all cases, we applied 0.5% isobaric bupivacaine and the following adjuvants: midazolam, clonidine or dexmedetomidine, and dexamethasone. We boosted the anesthesia with local ropivacaine due to inefficient sensory block in two patients. Nobody in the cohort received intravenous opioids, non-steroidal anti-inflammatory drugs, or additional sedation intraoperatively. Postoperative painkillers were upon the patient's request. No significant complications were detected. Conclusion: Thoracic spinal anesthesia incorporating adjuvants such as midazolam, clonidine or dexmedetomidine, and dexamethasone demonstrates not only efficient conditions for spine surgery, a favorable safety profile, high patient satisfaction, and intrathecal sedation but also effective opioid-free pain management.